Customer Attitude’s Model to Analyze Tempeh Products - Ilhamudin, M.; Masrun (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to find out the attitude of customers of one of the MSME products, namely tempeh which is widely spread in the city of Mataram. This study uses a sample survey method, by selecting several locations for making tempeh and places of sale as research locations. The research population is all tempeh consumers who come to make purchases at some of these centers, or consumers make purchases at other sales centers outside the industrial center. In determining respondents as the data source in this study, the researcher used purposive sampling techniques. Because the number of members of the study population is not known for sure, the number of research samples is determined to be 100 respondents. To answer the problem asked, the analysis tool used is the Ideal-Point Model, which is a customer's evaluation of what they feel and what they want. This model measures the difference between what is perceived and what consumers want. The results of the study show that the attitude of customers of tempeh products in Mataram city is very good. This is shown by the perception value of being in the upper interval class which means that tempeh products offered by producers in the city of Mataram are in accordance with customer desires.